Impact of Gonadotropin-Releasing Hormone Agonist Pre-treatment on the Cumulative Live Birth Rate in Infertile Women With Adenomyosis Treated With IVF/ICSI: A Retrospective Cohort Study - Chen, Minghui; Luo, Lu; Wang, Qiong; Gao, Jun; Chen, Yuqing; Zhang, Yingying; Zhou, Canquan (Frontiers in Endocrinology, 2020)
Introduction:Although pre-treatment with a GnRH agonist can reduce the size of adenomyosis lesions, the supra-physiological hormone level induced by controlled ovarian hyperstimulation (COH) may negate the usefulness of the GnRH agonist in patients with adenomyosis lesions, leading to continued poor outcomes in fresh embryo transfer cycles during IVF. It is unclear whether GnRH agonist pre-treatment before starting the long GnRH agonist protocol for IVF/ICSI can improve cumulative live birth rate (CLBR) of infertile women with adenomyosis. Method: In this retrospective cohort study, a total of 374 patients diagnosed as adenomyosis (477 cycles) underwent IVF/ICSI with long GnRH agonist protocol with or without GnRH agonist pre-treatment between January 2009 and June 2018. Logistic regression was used to assess the association between GnRH agonist pre-treatment and pregnancy outcome after adjusting for confounding factors. Results: The live birth rate in fresh embryo transfer cycles was higher in the non-pre-treatment group than in the GnRH agonist pre-treatment group (37.7% vs 21.2%, P=0.028); the adjusted odds ratio (OR) for the long agonist protocol without pre-treatment was 1.966 (95% CI 0.9-4.296, P=0.09). The cumulative live birth rate was higher in the non-pre-treatment group than in the GnRH agonist pre-treatment group (40.50% vs 27.90%, P=0.019); the adjusted OR for the long agonist protocol without pre-treatment was 1.361(95% CI 0.802-2.309, P=0.254). Conclusion: Our results indicated that GnRH agonist pre-treatment before starting the long GnRH agonist protocol does not improve the live birth rate in fresh embryo transfer cycles or cumulative live birth rate in infertile women with adenomyosis after IVF/ICSI treatment when compared to that in non-pre-treated patients. A subsequent prospective randomized controlled study is needed to confirm these results.